RESPON SISWA TERHADAP MULTIMEDIA INTERAKTIF LIDDLE (LINE AND ANGLE LEARNING) - Nurlaela Saadah; Dori Lukman Hakim (Akademika : Jurnal Teknologi Pendidikan, 2022)
The development of increasingly sophisticated technology will impact the field of education so that teachers are required to innovate in learning, one of which is by creating learning media. The selection of suitable learning media will attract students' interest in learning mathematics. Liddle interactive multimedia is an android application that aims to make it easier for students to understand line and angle material. This study aims to determine how students respond to interactive multimedia liddles on line and with angle material. This research was conducted at SMP Negeri 1 Jonggol with class VII I research subjects involving seven students. The research design used is descriptive research to describe students' responses to interactive multimedia Liddle. Data collection techniques in this study used student response questionnaires. While the analytical method used in this study is a semantic differential scale consisting of 4 scores. Based on the study results, it can be concluded that the interactive multimedia liddle received a positive response from students and was declared good to be used as a learning medium in the mathematics learning process. This is based on the results of the data from the aspects contained in interactive multimedia liddle get a percentage of 88.39% with the criteria of